2021
DOI: 10.1002/ddr.21808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non‐invasive brain stimulation on behavior and serum brain‐derived neurotrophic factor and insulin‐like growth factor‐1 levels in autistic patients

Abstract: Aberrant neural connectivity and intra‐cortical inhibitory dysfunction are key features of autism. Non‐invasive brain stimulation (NIBS) protocols have been proposed that modulate this aberrant plasticity. However, additional investigations are needed to evaluate the impact of this intervention on biological biomarkers of the disease. We recently demonstrated alterations in serum insulin‐like growth factor‐1 (IGF‐1) and brain‐derived neurotrophic factor (BDNF) immunoreactivity in subjects with autism compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Tables 1 and 2 show the demographic data and serum measurements for subjects with autism and controls. BDNF and IGF-1 measures from many of the subjects with autism were previously published as part of an analysis of non-invasive brain stimulation effectiveness in these patients 39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and 2 show the demographic data and serum measurements for subjects with autism and controls. BDNF and IGF-1 measures from many of the subjects with autism were previously published as part of an analysis of non-invasive brain stimulation effectiveness in these patients 39 .…”
Section: Resultsmentioning
confidence: 99%
“…All subjects had IQ scores within the normal range. Fifteen of the subjects with autism (Table 1 , subjects A1–A15) were included in previously published studies 38 , 39 .…”
Section: Methodsmentioning
confidence: 99%
“…BDNF is an activity-dependent neurotrophin regulating synaptic plasticity and the development of cortical connections [ 27 ]. BDNF acts via the pan-neurotrophin receptor (p75 NTR ), to which all mature neurotrophins bind, or the tropomyosin receptor kinase B (TrkB), to which it shows high affinity and specificity [ 28 ].…”
Section: Molecular Factors Common To Brain and Skin Developmentmentioning
confidence: 99%
“…Several articles focused on the genetics of response to an adverse reactions of medications used to treat psychiatric disorders (Maes et al, 2020; Ortega‐Vázquez et al, 2020; Rybakowski, 2020; Vorspan et al, 2021). One article investigated biological markers of response to noninvasive brain stimulation in Autistic patients (Robinson‐Agramonte et al, 2021), while two articles focused on neurodegenerative disorders, specifically on Parkinson's disease (Cacabelos et al, 2021) and multiple sclerosis (Sánchez et al, 2021). Finally, one article focused on the relevance for the pharmacology of neuropsychiatric disorders of the expression and localization of cytochrome genes in human tissues (Fanni et al, 2021).…”
mentioning
confidence: 99%
“…Robinson‐Agramonte et al (2021) explored if serum levels of two neurotrophic factors, Brain derived neurotropic factor (BDNF) and Insulin‐like growth Factor 1 (IGF1), could constitute biomarkers of response to noninvasive brain stimulation (NIBS) in patients with a diagnosis of autism spectrum disorder (ASD). This pilot study showed that the treatment determined an improvement in scores of clinical behavioral scales, which was associated with a slight decrease in BDNF but not IGF‐1 levels.…”
mentioning
confidence: 99%